Outer Code-Mixing Used by Rural High School Students at a Senior High School in Taraju - Nuranisa, Hiqni; Puspawati , Indah (Universitas Muhammadiyah Yogyakarta, 2022)
Outer code-mixing is very helpful to support English communication. Outer code-mixing happens when the speakers mix the first language with foreign languages for helping in communication. It can improve English skills to facilitate students to practice English inside and outside of the classroom. Moreover, the students in rural area especially hard to learn English because of some problems that faced them. The aim of this research is to investigate the reasons why students use outer code-mixing in their communication and what the advantages of the use of outer code-mixing as perceived by high school students are. The research used descriptive qualitative as the research design plus the research gathered from six high school students at a senior High School students in a rural area. In addition, individual interviews are used to gather the data. The findings revealed that outer code-mixing used by High School students at school is identified to practice English, to practice pronouncing English words, to improve speaking skill, to learn vocabulary, to sound more sophisticated, to achieve good English grades, and to learn English in a fun way. Furthermore, it identified the advantages of the use of outer code-mixing namely to comprehend English better, to improve students’ confidence in speaking, to facilitate in socializing, to gain new vocabulary, and to improve grammatical knowledge.